Secure Multifactor Authentication and Access Control Mechanism for Electronic Bill Service in a 5G Cloud-Fog Hybrid Architecture. (12th May 2022) - Guo, Zhenyang; Zhang, Yueyu; Cao, Jin; Ren, Xiongpeng; Zhao, Xingwen; Li, Hui
Abstract : The electronic bill service was greatly encouraged by electronic commerce and paperless bills. However, the massive authentication and authorization access requests from users in the electronic bill services cannot be efficiently processed by a conventional client/server-based scheme during the 5G era. This paper proposes a secure multifactor authentication and access control scheme tailored for electronic bill service in a 5G cloud-fog hybrid architecture. The proposed scheme can realize many security properties, including mutual authentication, privacy protection, batch authentication, authorization and revocation of authority, and resistance to multiple protocol attacks. Moreover, the scheme has the desired performance compared to similar schemes. Finally, we used BAN logic and Scyther to analyze and verify the proposed protocol, and the result shows that the proposed scheme is stable and can achieve the previous security goals.